Grain Boundaries Contribute to the Performance of Perovskite Solar Cells by Promoting Charge Separations - Peng Xu; Pengfei Wang; Minhuan Wang; Fengke Sun; Jing Leng; Yantao Shi; Shengye Jin; Wenming Tian (Nano-Micro Letters)
Highlights Sub-micrometer-resolved photocurrent mapping in operational perovskite solar cells, achieved through our home-built photoluminescence and photocurrent imaging microscopy, reveals enhanced photocurrent at grain boundaries compared to grain interiors. Local pump-probe femtosecond transient absorption and Kelvin probe force microscopy measurements corroborate the presence of a built-in electric field in the vicinity of grain boundaries that promotes electron–hole separation and the subsequent charge collection, thereby contributing to the performance of perovskite solar cells.